2023
DOI: 10.1002/mp.16455
|View full text |Cite
|
Sign up to set email alerts
|

A MC‐based anthropomorphic test case for commissioning model‐based dose calculation in interstitial breast 192‐Ir HDR brachytherapy

Abstract: Purpose To provide the first clinical test case for commissioning of 192Ir brachytherapy model‐based dose calculation algorithms (MBDCAs) according to the AAPM TG‐186 report workflow. Acquisition and Validation Methods A computational patient phantom model was generated from a clinical multi‐catheter 192Ir HDR breast brachytherapy case. Regions of interest (ROIs) were contoured and digitized on the patient CT images and the model was written to a series of DICOM CT images using MATLAB. The model was imported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…With this level of agreement, it can be concluded that the Monte Carlo dose recalculation pipeline can produce consistent TG186 simulations across both MC codes. To ensure the validity of the dose distributions following the TG186 commissioning recommendations, it would require a consensus test case similar to work published by Peppa et al (2023) for HDR brachytherapy, which was not yet available for LDR brachytherapy at the time of publication.…”
Section: Discussionmentioning
confidence: 99%
“…With this level of agreement, it can be concluded that the Monte Carlo dose recalculation pipeline can produce consistent TG186 simulations across both MC codes. To ensure the validity of the dose distributions following the TG186 commissioning recommendations, it would require a consensus test case similar to work published by Peppa et al (2023) for HDR brachytherapy, which was not yet available for LDR brachytherapy at the time of publication.…”
Section: Discussionmentioning
confidence: 99%
“…The WGDCAB is currently developing new clinically relevant test cases (GYN, head and neck, breast, and prostate) for the existing MBDCA TPS as well as some low-energy test cases for TPSs in development. A good example of such a clinically oriented test case for breast brachytherapy is based on the geometry published by Peppa et al 42 These will all be added to the Registry once available and fully tested. This report does not address certain other key issues raised in the TG-186 report.…”
Section: Limitations and Physicist Responsibilitiesmentioning
confidence: 99%